Natural Soap Making Training with Business-Economic Value for Communities in Kembangan District - Melzatia, Shinta; Safira, Safira; Amam, Amam; Badruzzaman, Jabar; Gumilar, Rangga Prebawa (CV. Proaksara Global Transeduka, 2025)
The need for environmentally friendly products that are safe for health is increasing, including natural soaps that are free of harmful chemicals. Kembangan sub-district has abundant potential resources such as palm or coconut oil as the basis for making soap, but has not been optimally utilized. This community service activity aims to empower the community through training in making natural soap with business-economic value. The implementation method starts from a needs survey, preparation of training modules, soap making practices, to marketing strategies. The training participants consisted of micro and small-scale home-based businesses. The evaluation results showed active participation reaching 90%, with 80% of participants successfully making quality soap and 70% interested in developing a natural soap business. The main obstacles are limited tools, materials, and mentoring time. However, through collaboration with business partners and the government, this training can support economic independence based on MSMEs and environmental conservation. This program also encourages the formation of new business communities and increases community capacity in digital production and marketing. In conclusion, this training is effective in improving skills and opening up business opportunities based on local potential in a sustainable manner in Kembangan District.